Crime and Partnerships - Svarer, Michael
This paper tests whether being convicted of a crime affects marriage market outcomes. While it is relatively well documented that crime hurts in terms of reduced future income, there has been little systematic analysis on the association between crime and marriage market outcomes. This paper exploits a detailed Danish register-based data set to fill this gap in the literature. The main findings are that male convicts do not face lower transition rates into partnerships as such, but they face a lower chance of forming partnerships with females from more well-off families. In addition males who are convicted face a significantly higher dissolution risk than their law abiding counterparts.crime, marriage, divorce